Analisis Pendapatan Usaha Tani Padi (Oryza sativa L.) Sawah Tadah Hujan Dan Penggunaan Sumur Bor - Hujemiati Hujemiati; Besse Dahliana; Hasmidar Hasmidar (JURNAL WACANA PERTANIAN, 2022)
This research was carried out in September-October 2020. in Kading Village, Barebbo District, Bone Regency. The selection of this location was done purposively. The farmers who will be sampled in this study are farmers whose irrigation systems use rain-fed and drilled wells in Kading Village, Barebbo District. The number of respondent farmers in each of these studies was determined purposively, each of which numbered 25 people per group so that the total number of respondents became 50 people. The data analysis used is quantitative analysis, namely analyzing the income and profits obtained by farmers from rainfed lowland rice farming and the use of drilled wells. Quantitative analysis is used in assessing the level of income and profits. The results of this study indicate that the average income received by rainfed lowland rice farmers is Rp. 19,234,905.5 while lowland rice farmers use drilled wells of Rp. 25,960,241.3 and the income received by rainfed rice farmers is Rp. 15,494,701.5, while lowland rice farmers use drilled wells of Rp. 21,271,846.6. The income and receipts of borehole rice farmers are greater than those of rainfed lowland rice farmers